PWE-074 Faecal calprotectin in predicting relapse in inflammatory bowel disease: a meta-analysis. (22nd June 2015) - Mohammed, N; Telakis, E; Subramanian, V
Abstract : Introduction: Faecal calprotectin (FCP) is a non-invasive marker of gastrointestinal inflammation. Its utility in the clinical management of inflammatory bowel disease (IBD) is under evaluation. We aimed to perform a meta-analysis of prospective studies in assessing the ability of baseline FCP for predicting relapse with 12 months in patients with Crohn's disease (CD) and ulcerative colitis (UC) in clinical remission. Method: Multiple electronic databases were searched including Pubmed, Embase and Ovid looking for studies providing data on relapse prediction in IBD using FCP. Pooled sensitivity, specificity, negative (LR-) and positive (LR=+ predictive value diagnostic odds ratio (DOR) and pooled area under the receiver operating characteristic (AUROC) was calculated. A random effects model was used and publication bias was assessed using Funnel plots and Egger's test and heterogeneity was assessed using Cochran's Q and the I 2 test. Results: 8 studies involving 507 patients with CD and 8 studies involving 587 patients with UC were included. The predictive value for a relapse within 12 months for baseline FCP in patients with CD was sensitivity 73% (64–80), specificity 78% (74–82), LR+ 2.9 (1.9–4.5), LR- 0.4 (0.2–0.6), DOR 10.1 (4.5–22.6) and AUROC 0.83 (±0.04). The cut off for baseline FCP used for the CD studies ranged from 130–340 µg/g. The predictive value for a relapse within 12 months for baseline FCP in patients with UC was sensitivity 72% (65–77), specificity 78% (74–83), LR+ 3.0 (2.3–4.0), LR- 0.4 (0.2–0.6), DOR 9.2 (5.4–15.7) and AUROC 0.82 (±0.03). The cut off for baseline FCP used for the UC studies ranged from 130–250 µg/g. There was significant heterogeneity (I 2 > 50%) for all the analysis likely because of the differences in relapse rates and FCP cut off values used. Conclusion: FCP is a simple non-invasive marker with the potential to predict replase in IBD. With pooled sensitivity and specificity under 80% for both CD and UC, its value may be mainly to identify low risk patients. However wide variations in the cut off values for FCP used in these studies makes it difficult to apply this to routine clinical practice. Serial measurements of FCP to check for a rise from baseline may be the way forward for future studies. Disclosure of interest: None Declared.